2016
DOI: 10.1504/aajfa.2016.080522
|View full text |Cite
|
Sign up to set email alerts
|

Share price behaviour around dividend announcements in Pakistan

Abstract: This paper investigates the information content (signalling) of dividend announcements by firms listed on the Karachi Stock Exchange (KSE) over the period 2005 to 2009. This sample period was selected in order to avoid contamination of the dividend signal with a capital gains tax effect Lasfer, 1995;Bell and Jenkinson, 2002) Moreover, there is some evidence of information leakage as significant unexpected returns were uncovered two days before the dividend announcements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…It is evident that the ex-bonus led to a positive reaction; although being a predetermined event, the market reaction could not sustain longer. These results are partly in line with (Al-Shattarat et al, 2018;Anwar et al, 2016;Khan et al, 2016).…”
Section: Quantitative Analysis and Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It is evident that the ex-bonus led to a positive reaction; although being a predetermined event, the market reaction could not sustain longer. These results are partly in line with (Al-Shattarat et al, 2018;Anwar et al, 2016;Khan et al, 2016).…”
Section: Quantitative Analysis and Discussionsupporting
confidence: 82%
“…On the other side, the literature on corporate announcements provides evidence of signaling theory as proposed by Ross (1977) and Walter (1963). Further, Al-Shattarat et al (2018), Anwar et al (2016), Khan et al (2016) provide evidence supporting the signaling theory in emerging markets. Considering these facts, one obvious question is whether this signaling theory applies to the pandemic-affected economic situation.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Ngoc et al (2016), investigated reaction of the stock price on both the dividend announcement date and the exdividend date, and found a positive effect of dividend announcement on the stock return around the announcement date, and that the stock price moved up as long as the ex-dividend date approaches and then starts decreasing from this date onwards. Khan et al (2016), investigated the information content of dividend announcements by firms listed on the Karachi Stock Exchange (KSE), and report that no significant unexpected returns can be earned on the announcement date by trading on dividend news in Pakistan. Budagaga (2020) examined the impact of cash dividends on the market value of banks listed in Middle East and North African (MENA) emerging countries, and the results revealed that current dividend payouts and dividend yield do not provide information relevant to the establishment of market values in MENA emerging markets; thus, they have no material impact on MENA banks' market values.…”
Section: Studies On Emerging and Frontier Marketsmentioning
confidence: 99%